Formation Stages of the Classifier of Block of Flats in Yerevan - Voskanyan, Viktoria (Scientific Papers of National University of Architecture and Construction of Armenia, 2023)
The article refers to the problems of classification of buildings in the field of housing. The work aims to highlight the stages of formation of the classification of apartment buildings in Yerevan. The material was developed based on experience accumulated in different countries, research of scientific literature, and Internet sources, using scientific methods of analysis, coordination, and classification. The factors affecting the price of a residential building were analyzed, the criteria of the order of comfort of the classificatory of residential buildings were studied, and the features of the classificatory creation were developed. Summarising the results, the design of the classificatory according to the stage model was justified, based on the principles of the design of multi-apartment residential buildings and the presented requirements, while at the same time identifying the remaining issues from the point of view of its implementation in the practical field. The resulting model of stages can be useful for the development of legislative regulations on the classification of multi-apartment buildings in the field of housing construction.